ANALISIS PERBANDINGAN METODE ALTMAN Z-SCORE, SPRINGATE DAN ZMIJEWSKI DALAM MEMPREDIKSI POTENSI KEBANGKRUTAN PT HANJAYA MANDALA SAMPOERNA TBK PERIODE 2018-2021 - tiyan_12; Juliana Putra, Tiyan; Mukri, Cotoro; Whisnu Hendratni, Tyahya (JIMP : Jurnal Ilmiah Manajemen Pancasila, 2024)
Bankruptcy is a condition which states that a company is in financial trouble and the company cannot fulfill its obligations and continue its business. Bankruptcy is usually characterized by the presence of financial problems that pose risks indicating management failure. The data used in this study are company financial reports published on the Indonesian Stock Exchange's website. An example of this study is Hanjaya Mandala Sampoerna 2018-2021. The purpose of this study is to determine whether there are differences in bankruptcy prediction between the Altman Z-Score, Springate and Zmijewski models. In determining the most accurate prediction model to predict the bankruptcy of Hanjaya Mandala Sampoerna Tbk. Based on the results of data analysis, it was concluded that the three models have the same level of accuracy for the Altman Z-Score, Springate and Zmijewski models, namely the accuracy value of 100%. In addition, based on other tests using the Shapiro-Wilk test, the t test shows that there are differences in predictions bankruptcy among the three models.